Titanium dioxide-based thick film gas sensor for hydrogen detection - Mohd Chachuli, Siti Amaniah (2020)
The need in detecting hazardous gases such as hydrogen has led to the development of simple, reliable and low cost of gas sensor for environmental monitoring and human safety. Excess amount of hydrogen in air can cause explosion, while longer exposure to the hydrogen can cause oxygen reduction in human body if the hydrogen replaces the oxygen in air. Therefore, the detection of hydrogen leakage has become essential issue in many industries. In detecting low concentration of hydrogen, a sensing material based on titanium dioxide (TiO2) nanoparticles has been proposed in this study. A glass powder, B2O3 also was added into TiO2 to obtain good adhesion of sensing film onto an alumina substrate. The TiO2-B2O3 paste was prepared by mixing the sensing material with the organic binder. The organic binder used in this study was prepared using linseed oil, m- xylene and α-terpineol. The TiO2-B2O3 gas sensor was developed using screen- printing technology to obtain porosity structures on the surface of the sensing film of a gas sensor, thus adsorption of the target gas will be increased and sensitivity of the gas sensor can be improved. Multi-walled carbon nanotube (MWCNT) and graphene nanoflakes with different ratios were added into TiO2-B2O3 paste to enhance the conductivity of the gas sensor and to investigate the characteristics of the gas sensor, in term of sensitivity, response time, recovery time, optimum operating temperature and repeatability and stability properties of gas sensor to the hydrogen. The fabricated gas sensor was exposed to 100 – 1000 ppm of hydrogen and tested at different operating temperature (28°C, 50°C, 100°C, 150°C, 200°C and 250°C). Based on the TGA analysis, the optimum annealing temperature for the sensing film was achieved at 500°C with annealing time in 30 minutes under ambient air. The crystallinity of the sensing film after annealing treatment has been verified using EDX and XRD. Results showed the optimum operating temperature for the TiO2-B2O3 gas sensor was occurred at 200°C. Additional of MWCNT into TiO2-B2O3 has reduced the operating temperature from 150°C to 100°C, while addition of graphene nanoflakes has improved the sensitivity of TiO2-B2O3 gas sensor to hydrogen. This study suggests that TiO2- G1-B2O3 gas sensor as a better gas sensor for 100 – 700 ppm of hydrogen, while TiO2-MWCNT5-B2O3 gas sensor as a better gas sensor for concentration above of 1000 ppm of hydrogen. Overall, TiO2-MWCNT5-B2O3 gas sensor is chosen as a promising material for gas sensor in detecting 100 – 1000 ppm of hydrogen at operating temperature of 100°C. The highest sensitivity values for TiO2-MWCNT5- B2O3 gas sensor was achieved at operating temperature of 250°C with sensitivity values are 6.97, 33.61, 67.64, 102.23 and 159.07 for 100 ppm, 300 ppm, 500 ppm, 700 ppm and 1000 ppm of hydrogen, respectively.